Anticancer activity of goniothalamin on oral cancer cells in vitro and in vivo / Fahme Abdul Kalk Saeed Kaid - Fahme Abdul Kalk, Saeed Kaid (2018)
Goniothalamin (GTN) is one of styryl-lactons naturally available compounds isolated from Goniothalamus macro-phyllus. It shows a selective cytotoxicity against variety of cancer cell lines with no significant cytotoxicity toward non-malignant cells. The aim of this study was to evaluate the activity of GTN against oral cancer cells in vitro and in vivo. Materials and Methods: in vitro part of study, anti-proliferative effect and cytotoxic screening of GTN was conducted on H400 oral cancer cells using MTT assay. The mechanism of apoptosis was studied by mitochondrial membrane potential, cytochrome c detection and caspase-3/7, -8 and -9 assays. The blockage of apoptosis and cell proliferation was investigated using NF-kb assay. As for the in vivo part of study, the haematological, biochemical and histoathological evaluation of GTN was investigated on selected organs (kidney, liver, lung, heart, spleen and brain) of Sprague Dawley (SD) rats using Acute and sub-acute toxicity tests. The anticancer activity of GTN was evaluated using 4NQO-induced oral cancer rat model at different doses of GTN; 25, 50, 100, 150 mg/kg. The carcinogenic agent administered intraperitoneally into rats in drinking water for 12 weeks and the GTN treatment started at the 13th week for 10 weeks. At the end of the experiments the animals were anesthetized and then blood samples were collected for haematological and biochemical analysis. And then autopsy was carried out for all rats and tongue of rats were harvested for gene expression, histopathological and immunohistochemistry analysis. Result: As for in vitro study, MTT assay findings showed that GTN exhibited selective cytotoxicity and inhibited the growth of H400 oral cancer cells via apoptosis in dose and time-dependent manner. Mitochondrial membrane potential assay revealed the release of mitochondrial cytochrome c into cytosol. Caspases assays revealed the activation of initiator caspase-9 and executioner caspase-3/7 in dose- iv dependent manners. This form of apoptosis was closely associated with the inhibition of NF-kb translocation from cytoplasm to nucleus. As for in vivo study, the acute toxicity revealed that the GTN lethal dose was 420 mg/kg and the LD50 was 42 mg/kg. The subacute test revealed no evidence of any treatment-related changes of the animals used in this study. As for the anticancer activity of GTN on rat oral cancer, the finding showed no significant differences between GTN different doses. In the GTN-treated animal, the tumor size was reduced comparing to the untreated animals. The findings showed that GTN inhibit the expression of Cyclin D1, Ki-67, Bcl-2 and p53 genes while a slight increase in the expression of β-catenin and E-cadherin genes that was observed. The findings also revealed that GTN induces apoptosis by upregulation of Bax and Casp3 genes and down-regulation of Tp53, Bcl-2, Cox-2, Cyclin D1 and EGFR. GTN and Cisplatin combination showed better results in inhibiting oral cancer than GTN or Cisplatin alone. Conclusion: This study provides scientific validation for the safety of GTN up to the highest dose level used in this study. The findings of current study indicated that GTN has the potential to act as an anticancer agent against oral cancer.